Functional Endoscopic Sinus Surgery in Chronic Rhinosinusitis: Impact of Anatomical Variations on Operative Safety and Correlation of CT Imaging with Nasal Endoscopy - Dr. Vivekkumar Makadiya; Dr. Krishna Makadia, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Anatomical variations of the paranasal sinuses influence the pathophysiology of chronic rhinosinusitis (CRS) and may increase operative risk during functional endoscopic sinus surgery (FESS). High resolution computed tomography (CT) is the imaging cornerstone, but its diagnostic yield vis à vis nasal endoscopy in the presence of variants remains debated. Methods: A prospective observational study of 52 adults with medically refractory CRS was undertaken at a tertiary otorhinolaryngology unit. All participants underwent pre operative non contrast CT (Lund–Mackay scoring) and diagnostic nasal endoscopy (Lund–Kennedy scoring), followed by standardised FESS. Anatomical variants, disease extent and peri operative complications were recorded. Diagnostic accuracy indices of CT were calculated against endoscopic findings. Results: Concha bullosa (50 %), deviated nasal septum (46 %) and agger nasi cells (31 %) were the commonest variants. CT correctly identified 88 % of osteomeatal complex obstruction and 83 % of maxillary sinus disease, but sensitivity fell to 69 % for the frontal sinus. Overall CT/endoscopy concordance was substantial (κ = 0.71). Variants significantly associated with persistent sinusitis included concha bullosa (p = 0.02) and agger nasi cells (p = 0.01). Concha bullosa also conferred greater odds of nasolacrimal duct (p = 0.02) and carotid artery (p = 0.05) injury, while septal spurs and polyps correlated with epistaxis (p < 0.03). Post operative complication rates were low (CSF leak 1.9 %; orbital injury 0 %). Conclusion: CT reliably delineates key variants and disease burden, but complementary nasal endoscopy remains essential—particularly for frontal recess and subtle mucosal pathology. Recognition of high risk variants (concha bullosa, agger nasi, accessory ostia) enables tailored surgical strategies that maximise safety without compromising disease clearance.